Reduced expression of circRNA hsa_circ_0067582 in human gastric cancer and its potential diagnostic values. Issue 3 (12th November 2019) - Yu, Xiuchong; Ding, Haixiang; Yang, Liangwei; Yu, Yu; Zhou, Jiaming; Yan, Zhilong; Guo, Junming
Abstract: Background: Gastric cancer (GC) is one of the global mortality diseases and has a poor prognosis due to the lack of ideal tumor biomarkers. Circular RNAs (circRNAs) are an abundant kind of endogenous RNAs that recently are found play a crucial role in the cancer occurrence and development. Nevertheless, little is known with regard to the diagnostic values of these circRNAs for GC. In this article of research, we investigated the role of hsa_circ_0067582 in clinical diagnosis of GC. Materials and Methods: We used divergent primers, and the expression levels of hsa_circ_0067582 in 93 fresh GC tissues and paired adjacent normal tissues from surgical patients were detected using quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Then, a receiver operating characteristic (ROC) curve was established to assess the diagnostic significance of hsa_circ_0067582. The relationship between expression of hsa_circ_0067582 and clinicopathological factors of patients was made further explored. Results: Hsa_circ_0067582 levels were significantly decreased in GC tissues contrasted with adjacent normal tissues (n = 93, P < .001). After that, we discovered that it was evidently downregulated in 81.7% (76/93) GC tissues. The area under the ROC curve (AUC) of hsa_circ_0067582 was up to 0.6937, the sensitivity was 66.67%, and the specificity was 61.29%. Moreover, the hsa_circ_0067582 levels were obviously associated with tumor diameter ( P = .002) and carbohydrate antigen 19‐9 (CA19‐9, P = .01). Meanwhile, after operation, low‐level group of hsa_circ_0067582 of GC patients was associated with better prognosis. Conclusion: Our data imply that hsa_circ_000067582 may be a potential biomarker for GC diagnosis and prognosis evaluation.